Variation in Seagrass-Associated Macroinvertebrate Communities Along the Gulf Coast of Peninsular Florida: An Exploration of Patterns and Ecological Consequences - Barry, Savanna C.; Hyman, A. Challen; Jacoby, Charles A.; Reynolds, Laura K.; Kowalewski, Michal; Frazer, Thomas K. (Frontiers in Marine Science, 2021)
Seagrasses form vast meadows of structurally complex habitat that support faunal communities with greater numbers of species and individuals than nearby unstructured habitats. The Gulf coast of peninsular Florida represents a natural laboratory ideally suited to the study of processes that shape seagrass-associated invertebrate and fish communities within meadows of a single species of seagrass, Thalassia testudinum. This suitability arises from a pronounced structural and chemical gradient that exists over ecologically relevant spatial and temporal scales, as revealed by extensive monitoring of water quality and seagrass. We hypothesized that seagrass-associated invertebrate communities would vary across five estuarine systems spread along a spatial gradient in phosphorus concentration, an important driver of seagrass and phytoplankton growth in this region. The quantitative results based on data acquired at 25 stations (75 samples, 52,086 specimens, and 161 taxa) indicated that each of the five estuarine systems were distinct with regard to species composition and differences among systems were driven by abundant or relatively common species. In addition, we found evidence to indicate food webs in seagrass meadows along this gradient may differ, especially in the relative dominance of algal grazers and predatory invertebrates. These changes in species composition and trophic roles could be driven by phosphorus directly, through increases in rates of primary production with higher concentrations of phosphorus, or indirectly, through nutrient-mediated changes in the physical structure of the seagrass canopy. Our results suggest that differences in the habitat created by T. testudinum under differing phosphorus supplies lead to ecologically significant shifts in macroinvertebrate communities.